Optimization of the fabrication of photonic crystal fiber for application as a scanning near-field optical microscope probe - Kua, Tennya Yen Fong. (2011)
The scanning near-field optical microscopy (SNOM) system is a comparatively recent microscopy system with superior capability for nano-structural investigations due to its ability to exceed the far-field diffraction limit by the use of evanescent waves. One of the major factors impacting the performance of a SNOM system is the probe being used, which is a critical component for evanescent wave transmission and detection. In this study, we aim to develop a fabrication method for photonic crystal fiber (PCF)-type fiber for use as SNOM probes. PCF type probes are relatively new in the field of optical microscopy, and detailed documentations of their fabrication are limited. Because PCF type probes offer substantial advantages over the current probes (aperture and aperture-less) used in near-field optics, there is a need to conduct an in-depth analysis in this area of research. By comparing and contrasting between 3 different fabrication methods - arc current, flame and CO2 laser method, we attempt to optimize experimental protocols and identify key parameters for PCF fiber fabrication, in order to build a technological platform for further related research. In this research paper, different experimental setups were built based on the 3 different probe fabrication techniques proposed. Critical setup parameters central to the experimental protocols were uncovered by optimizing a multitude of different factors. The probes fabricated were observed under a confocal microscope in order to compare and contrast the integrity and robustness of the probes produced from different setups. From the analysis of the results, effective probe fabrication is replicable using the arc current method, with the critical factors being the current applied and pressure build-up. However, with regards to the other 2 more novel fabrication methods, determination of critical parameters were more complex, and there were difficulties in reproduction of results. Therefore, further studies on optimization and control are recommended before accurate probe fabrication can be performed.